Biodegradability of Proteolytic Bacteria in Mangrove Ecosystems - Claudia, Kristiwany Mayneke; Nursyirwani, Nursyirwani; Effendi, Irwan (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2021)
The purpose of this study was to awareness the optimal time for the growth of proteolytic bacteria in producing the protease enzyme and determine the effectiveness of the protease enzyme from proteolytic bacteria in degrading mangrove litter. The method used was the experimental method by using two proteolytic bacteria isolates, namely Bacillus manliponensis (K6) and Bacillus toyonensis (K20). This method used one treatment for each proteolytic bacterial isolate, namely the addition of different extract containing protease enzyme (0%, 25%, and 50%) with three replications. Measurement of bacterial growth was carried out every 6 hours for 24 hours using Total Plate Count (TPC) and spectrophotometric method. B. manliponensis and B. toyonensis have enzyme activity as indicate by the presence of a clear zone on Zobell Marine Agar 2216 and skim milk 1%. The growth bacteria based on the TPC measurement was directly proportional to the spectrophotometric measurement results. The highest bacterial count was (1.39 x 108 CFU's/ml) K6 bacteria and (1.52 x 108 CFU's/ml) K20 bacteria. The results of the measurement of cell growth in the spectrophotometric method occurred at the 6th hour, namely 10.36 x 108 CFU's/ml (K6 bacteria) and 10.97 x 108 CFU's/ml (K20 bacteria). The optimum time of the protease enzyme occurred at 6 hours, which was 0.0258 mg/ml (K6 bacteria) and 0.0262 mg/ml (K20 bacteria). The highest dissolved protein content was obtained at the 50% dose of 0.054 mg/ml (K6 bacteria) and 0.055 mg/ml (K20 bacteria), while the lowest was at 0%, namely 0.050 mg/ml (K6 bacteria) and 0.051 mg/ml (K20 bacteria).